Valorização docente no município de João Pessoa: o papel do Sindicato dos Trabalhadores em Educação (2007-2017) - Assis, Valdegil Daniel de (2019)
This study analyzed the role of the Union in the effort for the valorization of the education professionals and the evolution of the salaries of teachers in the context of the Fund for maintenance and development of basic education and valorization of Education Professionals (FUNDEB) in the city of João Pessoa. We sought to understand how the union acted in the demand for implementing the policy of valuing the education professionals of this city, regarding the minimum professional wage level (PSPN) and the career and remuneration plan of the education professionals of the city of João Pessoa (PCCR) between 2007 and 2017. This period comprises the creation of the FUNDEB and extends until 2017, year of completion of this research, which took the field of historical-dialectical materialism as a basis for analyzing and understanding sources and reality, based on economic, political and social factors. The study is based in a qualitative research, with bibliographic and documentary sources, which allowed the compilation of theoretical productions about the educational public policies implemented in Brazil; also official documents, including the laws regulating the educational policy, and sources that allowed the reconstruction of the history of the union of education professionals of the city of João Pessoa. The analysis revealed that the Union played a contributory role in valuing the teachers in the city of João Pessoa, especially in their organization as a class, and in the implementation of the and the career and remuneration plan of the education professionals, an advancement that granted better teacher recognition, and more quality in education. Regarding salary developments, it was found that the guarantees in the legislation, together with the Union's actions aiming to guarantee workers' rights, resulted in significant advances in the teachers’ remuneration between the years 2007 and 2014, especially between 2010 and 2014, with readjustments equal to or higher than the PSPN. In contrast , from 2015 onwards there was a reduction in wage gains due to the economic crisis allied to the national political crisis.